(untitled) - Gerstmann, Evan (Cambridge, 2004)
In this provocative legal study, Gertsmann drills deep into the gay marriage debate, beyond the well-mined rhetoric of "gay rights," to focus on the true bedrock of Americans' freedom: the Constitution. According to the author, one of the most important issues challenging the Constitution's promise of legal equality is same-sex marriage. "Marriage was one of the first fundamental rights the Court recognized," writes Gertsmann. "Far from being limited to a racial context, it has been applied to individuals whom society has every reason to punish, individuals whose fitness for marriage and parenthood could be doubted." So why has same-sex marriage remained the exception to this fundamental right to marry? Early in the text, Gertsmann wisely concedes that it is not "irrational" for a society to ban same sex marriage, because legalizing these unions could be seen as an endorsement of homosexual relationships, much like legalizing heroin could be seen as a government endorsement of drug use. But while Gertsmann offers an understanding of why society is dragging its heels to the gay-marriage altar, he argues that giving gay couples marriage licenses no more endorses their homosexuality than giving them driver's licenses does. "In each case, the state is simply granting certain benefits to its citizens without respect to their sexual orientation," he writes. The author's balanced, well-measured defense of same-sex marriage argues that the most personal of decisions (whom we marry) will continue to be treated as a public act and, therefore, will continue to be stymied by government interference until the courts consider the right to marry with "the same rigor and consistency" that they apply to another touchstone of the Constitution: freedom of speech.
Keywords: Same-sex marriage,Constitutional law,Hôn nhân đồng tính,Hiến pháp; Law and legislation,Luật và pháp luật; United States,United States,Hoa Kỳ,Hoa Kỳ